Estetika Garap Tubuh dan Properti dalam Karya Tari Gandhewa Raga - Wibowo, Anggono Kusumo; samsuri, samsuri (Institut Seni Indoensia Surakarta, 2022)
ABSTRACTThe dance entitled Gandhewa Raga is a group dance of men and women. This dance is worked on with the beauty of the body and operatives. The body functions as a medium to express the contents of dance and property, as one of the media, said the complement. Disclosure of the beauty of the body worked with property media, namely gandhewa. The motion displayed is the exploration motion of the gandhewa form. The movement of Gandhewa Raga dance is a movement of the Surakarta stout and princess style traditions. This work process aims to explore, find out the meaning of property, and understand the aesthetic values of the body and property. The results of this study are explorations and disclosures of body and property values. The method used is creating dance work with the process of investigation, improvisation, and composition. The aesthetic of the Gendhewa Raga dance will emerge after carrying out the stages of the method. The aesthetic value of body and property can be seen from the form of dance composition that has been arranged and can be enjoyed. This beauty can be enjoyed by aspects of dance movements, namely energy, space, and time, dance accompaniment, fashion make-up, dance performers, staging venues, and property processing. Keyword: Gandhewa Raga, Aesthetic, Phsycal dance, body and property ABSTRAKTari Gandhewa Raga merupakan tari kelompok putra dan putri. Tarian ini merupakan tari yang digarap dengan keindahan tubuh dan poperti. Tubuh yang berfungsi sebagai media untuk mengungkapkan isi tari da propertisebagai salah satu media ungkap pelengkapnya. Pengungkapan keindahan tubuh digarap dengan media propert yaitu Gandhewa. Gerak yang ditampilkan adalah gerak eksplorasi dari bentuk Gandhewa. Gerak karya tari Gandhewa raga adalah gerak tradisi gaya Surakarta gagah dan putri. Proses kekaryaan ini bertujuan untuk bereksplorasi, mengetahui makna properti, dan memahami nilai-nilai estetis tubuh dan property. Hasil penelitian ini merupakan eksplorasi dan pengungkapan nilai tubuh dan properti. Metode yang digunakan adalah metode menciptakan karya tari dengan proses eksplorasi, improvisasi dan komposisi. Estetika ketubuhan tari Gandhewa Raga akan muncul setelah melaksanakan tahapan metode tersebut. Nilai estetis ketubuhan dan propertidapat dlihat dari bentuk koposisi tari yang sudah tersusun dan sapat dinikmati. Penikmatan keindahan tersebut dapat dilihat dengan aspek gerak tari yaitu tenaga, ruang dan waktu, serta iringan tari, tata rias busana, pelaku tari, tempat pementasan dan pengolahan properti Kata kunci: Gandhewa Raga, Estetika, Tari Fisik, Tubuh dan Properti